Recombinant covalently closed circular DNA of hepatitis B virus induces long‐term viral persistence with chronic hepatitis in a mouse model. Issue 1 (15th November 2017) - Li, Gaiyun; Zhu, Yuanfei; Shao, Dianhui; Chang, Hao; Zhang, Xiaoming; Zhou, Dongming; Gao, Yueqiu; Lan, Ke; Deng, Qiang
Abstract : Covalently closed circular DNA of hepatitis B virus (HBV) is critical for viral persistence in vivo . We recently reported a technique involving recombinant covalently closed circular DNA (rcccDNA) of HBV by site‐specific DNA recombination. Using hydrodynamic injection, rcccDNA induces a temporarily prolonged HBV antigenemia in immunocompetent mice, similar to acute resolving HBV infection. In this study, we simulated the pathophysiological impact of chronic hepatitis to reproduce rcccDNA persistence in mouse models. We showed that rcccDNA achieved long‐lasting persistence in the presence of a compromised immune response or when transcriptional activity was repressed. To closely mimic chronic hepatitis, we used a replication‐defective recombinant adenoviral vector to deliver rcccDNA to the liver, which led to prominent HBV persistence throughout the experiment duration (>62 weeks) in transgenic mice expressing Cre recombinase under the albumin promoter. A sustained necroinflammatory response and fibrosis were identified in mouse livers, with dysplastic lesions commonly seen during the late stage of viral persistence, analogous to the progressive pathology of clinical chronic hepatitis. Conclusion: rcccDNA was intrinsically stable in vivo, enabling long‐term persistence in the context of chronic hepatitis, and viral persistence, in turn, may promote progression of chronic liver disease; our study also presented a surrogate model of HBV cccDNA persistence in mice that could advance our understanding of the pathogenesis of chronic hepatitis B. (Hepatology 2018;67:56‐70).